2022
DOI: 10.3390/diagnostics12081999
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Performance of Different Laboratory Methods for Measuring Susoctocog-Alfa

Abstract: Recombinant porcine factor VIII (rpFVIII) is indicated for treating bleeding episodes in acquired haemophilia A, but there are few data regarding laboratory methods to adequately monitor treatment. This study involving three Italian laboratories aimed to evaluate the analytical performance of different assays for measuring rpFVIII. Five spiked rpFVIII samples (0.5–1.5 IU/mL) were analysed on three days, in triplicate, with eleven combinations of reagents (Werfen, Boston, MA, USA: SynthasIL and SynthaFax for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Calibration of bCSA with human FVIII resulted in a 50% lower recovery of rpFVIII. A recent study has shown that the use of a chromogenic assay with a porcine calibrator and VWF‐containing FVIII‐deficient plasma provides satisfactory results 13 . We found a recovery of 70%−120% for the combination of bCSA with rpFVIII calibration.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Calibration of bCSA with human FVIII resulted in a 50% lower recovery of rpFVIII. A recent study has shown that the use of a chromogenic assay with a porcine calibrator and VWF‐containing FVIII‐deficient plasma provides satisfactory results 13 . We found a recovery of 70%−120% for the combination of bCSA with rpFVIII calibration.…”
Section: Discussionsupporting
confidence: 53%
“…A recent study has shown that the use of a chromogenic assay with a porcine calibrator and VWFcontaining FVIII-deficient plasma provides satisfactory results. 13 We found a recovery of 70%−120% for the combination of bCSA with rpFVIII calibration. The recovery was only 50%−80% in our patients with a rpFVIII inhibitors below the detection limit and the recovery of rpFVIII was further influenced by the presence of detectable inhibitory antibodies against human and porcine FVIII.…”
Section: Ratio Of Spiked/measured Fviii (%) Available Plasma Samples (N)mentioning
confidence: 64%
“…One recent study has used porcine FVIII to prepare the calibration curve and compared it to HemosIL human plasma calibrator. Recovery was improved by use of the porcine calibrator 6 highlighting how different reagent and standard combinations lead to variation within the results obtained. It is, therefore, important for laboratories to perform their own assessments of their assay's performances in patients receiving rpFVIII treatment.…”
Section: Discussionmentioning
confidence: 99%
“…OSA are known to vary in FVIII:C and FIX:C levels measured in many modified FVIII and FIX concentrates. A recent small study of five spiked plasma samples with rpFVIII highlighted the differences obtained when using plasma calibrators, porcine standards and FVIII deficient plasma with and without VWF 6 when measuring rpFVIII by two OSA (Synthasil and SynthAFax) and CSA (Coamatic FVIII). In a worldwide laboratory field study using spiked samples, CSA have been shown to underestimate rpFVIII 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The latter has recently been licensed for management of acute bleeding in AHA [9] based on a prospective study in adult patients with major bleedings [10]. rpFVIII advantages include the possibility of monitoring response with standard coagulation laboratory assays and minimizing thrombotic risk [11][12][13][14][15]. Thromboembolic risk is, indeed, increased in patients treated with bypassing agents, particularly the elderly and those with underlying pro thrombotic conditions (i.e., previous thrombosis, immobilization, malignancy, indwelling catheters, surgery, and pregnancy/post-partum) [7,16,17].…”
Section: Introductionmentioning
confidence: 99%